A critical analysis of the strategies of terminology creation in the context of a multilingual Namibia: the case of ruManyo - Mukoya, Angelika Mate (School of Languages and Literatures, 2023)
This study examines the strategies used to develop terms in the language ruManyo. The study focuses on existing strategies used by language practitioners to construct analogous key-concept terms in ruManyo for application in various fields. The sample was taken through purposive sampling, and the investigation was carried out in Namibia's Kavango East region, in domains such as education, radio, agriculture, law, hospital, bank, and church. The data for this report was collected using a case study, which included document analysis, participant observations and interviews with ruManyo language practitioners. The findings of the study indicate that ruManyo language practitioners lack the skills and information needed to build appropriate terminology solutions for specific domains. Furthermore, it appears that linguistic competence is not guiding word-generation efforts in certain disciplines. The study re-evaluated the evolution of multilingual word-generation techniques, and discovered that specific domains necessitate specific tactics, based on the context in which terms are employed. Based on the findings of this study, the recommendation is to design unambiguous wordinvention strategies for specific domains that are consistent with the terminology development guidelines for indigenous African languages. Due to the deficiencies in African indigenous language terminologies highlighted in this study, the researcher proposes the creation of a manual for ruManyo, detailing each method for application in different domains.